Authoring adaptive educational hypermedia on the semantic desktop. (18th October 2007) - Hendrix, Maurice; Cristea, Alexandra; Nejdl, Wolfgang
Personalisation of information is a desired feature, but authoring and creation of adaptive hypermedia is a difficult endeavour. Especially, manual annotation is the bottleneck of such authoring. Thus it is vital to support the authoring process by reusing automatically generated metadata. Here, we show the integration of the generic AH authoring environment MOT into a semantic desktop environment, as well as its first small-scale evaluation. In this set-up, the semantic desktop environment provides the rich source of automatically generated metadata, while MOT allows enhancing this metadata manually, as needed for the authoring of an adaptive environment ? here, an adaptive course.